PERHITUNGAN KESTABILAN LUBANG BUKAAN PADA TEROWONGAN HEADRACE PLTA SINGKARAK MENGGUNAKAN ANALISIS BALI - Setyawan , Rudy
During construction of underground structure such as pressure tunnel, power house cavern, etc. Field measurement should be performed during construction phase for monitoring structure stability and updating design parameters. The constrains are found during field and laboratory test. In another hand is difficult to carry a proper analysis for verification a result of field and laboratory test. Such conditions are found at Singkarak HEPP which is only 4 bore holes for 16.5 km stretch of tunnel. Therefore displacement measurements should be performed along the tunnel stretch during the construction for updating the parameter used for initial design. Improving initial design for elaborated field measurement result adopted back analysis method. Provided the used of SAP90 for solving finite element analysis, initial step is establishing physical model for restrain boundary to represent actual field conditions instead of geometry, geomechanic characteristic of the materials, loading and boundary restraint from the model. Loading at tunnel base on result of hydraulic fracturing test where for the model 1 the overburden pressures are constant and the maximum horizontal stress applied, for model 2 the overburden pressures are constant and the minimum horizontal stress applied. Trial and error should be done during back analysis process by adjusting modulus elasticity value until displacement program output similar to the field measurement. The back analysis output showed modulus elasticity value and the plastic zone thickness is defined in constant overburden pressure affected by horizontal stress. In case maximum horizontal stress applied modulus elasticity has a tendency above the middle elasticity value present rock. In case minimum horizontal stress applied modulus elasticity have a tendency below the middle elasticity value present rock. Most of the sidewall will go in plastic zone if maximum horizontal stress applied and most of crown and invert will go in plastic zone if minimum horizontal stress applied. Along the monitoring point modulus elasticity has different value therefore appropriate supporting system should be choose according to actual condition. Considering elasticity behavior supporting system should be modified from local rock bolt to arch building bolting or erected steel ribs, because local rock bolt only improving slightly safety factor value